Republic of Serbia : Staff Report for the 2014 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that the Serbian economy is facing serious challenges. GDP contracted by an estimated 2 percent in 2014 on account of continued falling domestic demand aggravated by floods, and weak economic activity in trading partners. This, together with the low imported inflation, pushed Serbia's inflation rate below the National Bank of Serbia's inflation tolerance band, allowing some easing of monetary policy. To support their economic policies over 2015-17, the authorities have requested the IMF's assistance. The program aims to restore public debt sustainability, strengthen competitiveness and growth, and boost financial sector resilience.